(untitled) (Journal of Mathematical Study, 2024)
In this paper, for given mass c>0, we study the existence of normalized solutions to the following nonlinear Kirchhoff equation cases (a+b_R^3[| abla u|^2+V(x)u^2]dx)[-Δ u+V(x)u]=λ u+μ|u|^q-2u+|u|^p-2u, in R^3, _R^3|u|^2dx=c^2, caseswhere a>0, b>0, λ∈R, 5